2012
DOI: 10.2351/1.4730803
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hybrid microgels by coupling of laser ablation and polymerization in aqueous medium

Abstract: Loading microgels with bioactive nanoparticles (NPs) often requires multiple synthesis and purification steps, and organic solvents or precursors that are difficult to remove from the gel. Hence, a fast and aqueous synthesis procedure would facilitate the synthesis of inorganic–organic hybrid microgels. Two microgel compounds were hybridized with laser-generated zinc oxide (ZnO) NPs prepared in a single-step procedure. ZnO NPs were formed by laser ablation in liquid, while the polymer microgels were synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 64 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…Resano-Garcia et al reported that the yield of LAL-synthesized AgNPs in stirred liquid was approximately 30% higher than that in unstirred liquid, that the ablation reproducibility was also significantly improved (over four repeated experiments), and that the NP size distribution was narrower (Figure 53a,b). 401 Similar findings were reported by researchers using a semibatch apparatus equipped with a magnetic stirrer 380,738 (Figure 52b) and single-pass flowing liquid experimental configurations 310 (Figure 52c). The removal of NPs by flowing liquid is effective and inhibits bubble settlement in the vicinity of the ablation grooves, 400 thereby improving the ablation reproducibility and dramatically increasing the NP productivity (by 380% for ns LAL of alumina and 700% for fs LAL of gold) relative to the stationary liquid by adjusting the flow rate.…”
Section: Chemical Reviewssupporting
confidence: 87%
“…Resano-Garcia et al reported that the yield of LAL-synthesized AgNPs in stirred liquid was approximately 30% higher than that in unstirred liquid, that the ablation reproducibility was also significantly improved (over four repeated experiments), and that the NP size distribution was narrower (Figure 53a,b). 401 Similar findings were reported by researchers using a semibatch apparatus equipped with a magnetic stirrer 380,738 (Figure 52b) and single-pass flowing liquid experimental configurations 310 (Figure 52c). The removal of NPs by flowing liquid is effective and inhibits bubble settlement in the vicinity of the ablation grooves, 400 thereby improving the ablation reproducibility and dramatically increasing the NP productivity (by 380% for ns LAL of alumina and 700% for fs LAL of gold) relative to the stationary liquid by adjusting the flow rate.…”
Section: Chemical Reviewssupporting
confidence: 87%
“…Set-up for laser-fabrication of ligand-free palladium nanoparticles in aqueous, micromolar saline solution. see also [32]). The chamber was filled with Milli-Q water (resistivity of 18.2 M cm at 25 • C) or with an electrolyte solution using different ionic strengths.…”
Section: Laser Ablation and Nanoparticle Adsorptionmentioning
confidence: 91%
“…Ablation was conducted in a self-constructed ablation chamber (Fig. 2 ), which has been shown in more details by Nachev et al [ 52 ]. A system containing a ns-pulsed Nd:YAG Laser (Rofin PowerLine E20) and a scanner with an F-Theta lens was chosen to generate the nanoparticles as described by Koenen et al [ 53 ].…”
Section: Methodsmentioning
confidence: 99%